2020
DOI: 10.1111/mec.15390
|View full text |Cite
|
Sign up to set email alerts
|

Time spent in distinct life history stages has sex‐specific effects on reproductive fitness in wild Atlantic salmon

Abstract: In species with complex life cycles, life history theory predicts that fitness is affected by conditions encountered in previous life history stages. Here, we use a 4‐year pedigree to investigate if time spent in two distinct life history stages has sex‐specific reproductive fitness consequences in anadromous Atlantic salmon (Salmo salar). We determined the amount of years spent in fresh water as juveniles (freshwater age, FW, measured in years), and years spent in the marine environment as adults (sea age, SW… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 71 publications
0
36
0
Order By: Relevance
“…, see also,Barson et al 2015). Given that larger size at a given sea age is indicative of higher performance and fitness in adult salmon (e.g.,Fleming 1996;Mobley et al 2020), the six6*L allele (being linked to larger size) may be expected to have a selective advantage over the E allele and is hence predicted to prevail within and among populations as a result of directional selection. However, the six6 genomic region is highly variable within and among populations(Barson et al 2015, Pritchard et al 2018, and balancing selection appears to be the pervasive mode of evolution, with both alleles exerting fitness advantage with different life-history strategies(Barson et al 2015).…”
mentioning
confidence: 99%
“…, see also,Barson et al 2015). Given that larger size at a given sea age is indicative of higher performance and fitness in adult salmon (e.g.,Fleming 1996;Mobley et al 2020), the six6*L allele (being linked to larger size) may be expected to have a selective advantage over the E allele and is hence predicted to prevail within and among populations as a result of directional selection. However, the six6 genomic region is highly variable within and among populations(Barson et al 2015, Pritchard et al 2018, and balancing selection appears to be the pervasive mode of evolution, with both alleles exerting fitness advantage with different life-history strategies(Barson et al 2015).…”
mentioning
confidence: 99%
“…The age at smoltification has direct effects on sea age (Box 1) and reproductive fitness. Earlier smolting individuals tend to spend more time at sea before returning to rivers to spawn (Erkinaro et al, 2019;Jonsson & Jonsson, 2011;Salminen, 1997) and have higher reproductive fitness due to generally achieving larger size (Mobley et al, 2020). There may also be a sexspecific relationship between growth and time spent in fresh water.…”
Section: Smoltificationmentioning
confidence: 99%
“…For example, females that spend more time in fresh water show reduced pre-and post-smolt (Box 1) growth (Einum et al, 2002), signifying a trade-off between growth at sea and the time spent in fresh water. A recent study demonstrated that females that spend more time in fresh water spend less time at sea than earlier smolting individuals, and suffer a reduction in reproductive success (Mobley et al, 2020). However, smolting early potentially exposes these individuals to higher predation at sea, highlighting a potential tradeoff between smolting and survival (McCormick et al, 1998).…”
Section: Smoltificationmentioning
confidence: 99%
See 2 more Smart Citations